Disassembly to order system under uncertainty - Kongar, E; Gupta, SM (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
This paper presents a multi-criteria optimization model of a disassembly-to-order (DTO) system under uncertainty. The goal of the proposed model is to determine the best combination of the number of each product type to be taken back from the last user and/or collectors. The EOL products are then disassembled for the retrieval of reusable components and materials and resold in order to meet a certain level of demand under a variety of physical, financial and environmental constraints. The surplus components are recycled, stored for usage in subsequent periods or properly disposed. The problem is modeled as a multi-criteria decision-making problem under uncertainty, where the aspiration levels for various goals are more likely to be in the approximately more (less) than and/or more (less) is better form. We employ fuzzy goal programming technique to solve the problem. When solved, the model provides the number of EOL products to be taken back as well as the number of items reused, recycled, stored and disposed. The values of a host of other performance measures are also obtained, including total profit, materials and items sales revenues, take back cost, transportation costs as well as costs of preparation of EOL products, destructive disassembly, non-destructive disassembly, recycling, storage and disposal. A case example is presented to illustrate the model's implementation. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: fuzzy goal programming; multiple criteria decision-making; environmentally conscious manufacturing; disassembly; end-of-life processing; GOAL PROGRAMMING PROCEDURE; FUZZY GOALS; PRODUCTS; DESIGN; PARTS; Business & Economics; Operations Research & Management Science